Competency Reskilling Model for Improved Performance of TVET and Science Workshop Managers in Higher Institutions - Sunday rufus Olojuolawe; Adewumi Moradeke Grace; Akinwumi Omolola Ibukun; Ajisola Kolawole Thomas (Universitas Diponegoro, 2022)
The existence of the workshop attendants in technical education is aimed at complementing the job of the lecturers to ensure that a well-grounded and employable graduate is produced. Over the years, the complaints about the poor quality of the output have been shifted to the lecturers teaching methods and techniques, workshops and facilities without recourse to the competencies of the workshop attendants. The focus of this study is to develop a model that will boost the technical proficiency of the personnel that is employed to work in the technical workshops and laboratories. The exploratory sequential mixed method was used for the study. 8 participants were involved in the qualitative phase of the study while the quantitative phase involved 44 respondents from among the Workshops experts and Academics. The sample for the study was selected from among the workshop attendants and academics in the 3 universities and 4 Colleges of Education in South-Western Nigeria. The validity and reliability of the instrument were achieved through subject matter experts from the Industry and Academics, and the Fleiss Kappa calculator, which gave reliability of 85.83%. The purposive sampling technique was used for the qualitative phase. The Rasch Measurement Model was used to analyze the item in the instrument by examining the person and item separation and reliability, dimensionality, item fit statistics to determine the item that fits the model using the Partial Credit Model. The item in the instrument was recorded an item separation of 3.32 with a reliability of .92. The model will have implications for the Universities, the technicians, the students and society.